Few-Shot Induction of Generalized Logical Concepts via Human Guidance - Das, Mayukh; Ramanan, Nandini; Doppa, Janardhan Rao; Natarajan, Sriraam (Frontiers in Robotics and AI, 2020)
We consider the problem of learning generalized first-order representations of concepts from a small number of examples. We augment an inductive logic programming learner with two novel contributions. First, we define a distance measure between candidate concept representations that improves the efficiency of search for target concept and generalization. Second, we leverage richer human inputs in the form of advice to improve the sample-efficiency of learning. We prove that the proposed distance measure is semantically valid and use that to derive a PAC bound. Our experiments on diverse learning tasks demonstrate both the effectiveness and efficiency of our approach.